Psychology of Coloured People: A Critical Note to the Dominance of Euro-American-Oriented Psychology over the Psychology of Non-Western Countries - Steinmetz, Carl H. D. (Advances in Social Sciences Research Journal, 2022)
Whether psychology is universally or regionally determined is examined in this article. Implicitly, this question is about the general validity of statements of psychological research, theories and practices (such as testing, therapy, recruitment, etc.). If psychology is culturally and regionally rooted, statements based on psychological research, theory and practice are not universally valid. Moreover, once it is established that psychology is cultural and regional in nature, the underlying question arises: is there a psychology of coloured and white people? The findings of this article are based on a reasoned literature review. First of all, the origins of Western psychology are in broad terms mapped out. In the period between and after the first and second European and Asian World Wars, American and European psychologists made psychology big and important. Psychology had the wind in its sails because the American defence put an immense amount of money into test, social and clinical psychology. This was necessary to be able to select soldiers, maintain an army and take care of veterans. The Americans then used this Psychology to colonise the world (especially the non-Western world). With that, the original psychology from the non-Western world has gone into the ’dustbin’. Only now the non-Western world is rediscovering that their millennia-old psychology needs to be taken out of the ‘dustbin’. That ancient non-Western psychology rooted in philosophy is mapped out in this article for China, India and Africa. The tentative conclusion is that psychology is regionally and culturally determined. We could call this psychology holistic psychology. After all, we humans represent and are humanity as a whole, our ancestors, born and unborn children, gods and spirits, mother earth (fauna and flora) and the cosmos. In this psychology there is also room for spirituality and consciousness. In fact, there is a psychology of and for people of colour anywhere in the world. It is not clear whether this also applies to the research methods.